Two new non-chlorophyll f-producing species in the Kovacikia genus (Leptolyngbyaceae, Leptolyngbyales) from the Poyang Lake Basin, China - Shen, Li-Qin; Dai, Guofei; Le, Ying; Lai, Sheng; Liu, Xinyuan; Li, Renhui; Liu, Jutao (Frontiers in Microbiology, 2025)
For the filamentous cyanobacteria, the order Leptolyngbyales is the larger and obviously polyphyletic group, although its members are morphologically similar. In this study, three Leptolyngbya-like strains were isolated from the soil of three different habitats in the Poyang Lake Basin, China—dark microhabitats similar to those found in far-red light (FRL) habitats. The three strains were phylogenetically identified as Kovacikia diezihuensis sp. nov. and Kovacikia jiangxiensis sp. nov. (Leptolyngbyaceae, Leptolyngbyales) using a polyphasic approach, respectively. The phylogenetic tree showed that they clustered within the Kovacikia genus (species type: Kovacikia muscicola) with five other Kovacikia species. The 16S rRNA gene sequences of K. diezihuensis and K. jiangxiensis shared 97.2% similarity with each other (data not shown) and 94.9–96.8% similarity with five other Kovacikia species. Furthermore, the secondary structures of the internal transcribed spacer (ITS) regions and ITS sequences exhibited uniqueness. The two species were similar to the other five Kovacikia species in morphology, but K. diezihuensis was bright blue-green, and K. jiangxiensis was gray-green to blue-green in color, and its length was usually greater than its width in cells under white light, respectively. Pigment analysis showed that the two strains did not produce phycoerythrin. FRL adaptation experiments further showed that they could neither grow nor produce chlorophyll (Chl) f under FRL. In summary, K. diezihuensis and K. jiangxiensis were new non-Chl f-producing species in the Kovacikia genus. This is the first report of both Chl f-producing and non-Chl f-producing species in the same genus within the Leptolyngbyales, shedding light on the diversity and the evolutionary divergence of Chl f-producing cyanobacteria.